Female Sex and Angiotensin-Converting Enzyme (ACE) Insertion/Deletion Polymorphism Amplify the Effects of Adiposity on Blood Pressure. Issue 1 (January 2022) - Chiriacò, Martina; Tricò, Domenico; Leonetti, Simone; Petrie, John R.; Balkau, Beverley; Højlund, Kurt; Pataky, Zoltan; Nilsson, Peter M; Natali, Andrea
Abstract : The pathophysiological link between adiposity and blood pressure is not completely understood, and evidence suggests an influence of sex and genetic determinants. We aimed to identify the relationship between adiposity and blood pressure, independent of a robust set of lifestyle and metabolic factors, and to examine the modulating role of sex and Angiotensin-Converting Enzyme (ACE) insertion/deletion (I/D) polymorphisms. In the Relationship Between Insulin Sensitivity and Cardiovascular Disease (RISC) study cohort, 1211 normotensive individuals, aged 30 to 60 years and followed-up after 3.3 years, were characterized for lifestyle and metabolic factors, body composition, and ACE genotype. Body mass index (BMI) and waist circumference (WC) were independently associated with mean arterial pressure, with a stronger relationship in women than men (BMI: r =0.40 versus 0.30; WC: r =0.40 versus 0.30, both P <0.01) and in individuals with the ID and II ACE genotypes in both sexes ( P <0.01). The associations of BMI and WC with mean arterial pressure were independent of age, sex, lifestyle, and metabolic variables (standardized regression coefficient=0.17 and 0.18 for BMI and WC, respectively) and showed a significant interaction with the ACE genotype only in women ( P =0.03). A 5 cm larger WC at baseline increased the risk of developing hypertension at follow-up only in women (odds ratio, 1.56 [95% CI, 1.15–2.10], P =0.004) and in II genotype carriers (odds ratio, 1.87 [95% CI, 1.09–3.20], P =0.023). The hypertensive effect of adiposity is more pronounced in women and in people carrying the II variant of the ACE genotype, a marker of salt sensitivity. Abstract : Supplemental Digital Content is available in the text.